First pathological report of a de novo CD5‐positive diffuse large B‐cell lymphoma patient presenting with Guillain–Barré syndrome‐like neuropathy due to neurolymphomatosis. Issue 4 (2nd May 2018) - Kobayashi, Mikiko; Sakai, Yasuhiro; Kariya, Yuta; Sakai, Hitoshi; Hineno, Akiyo; Oyanagi, Kiyomitsu; Kanno, Hiroyuki
Abstract : Peripheral neuropathy occurs in approximately 5% of the patients with lymphoma. Two major causes of peripheral neuropathy associated with lymphoma are neurolymphomatosis and paraneoplastic neuropathy such as demyelinating neuropathy. The differential diagnosis between neurolymphomatosis and demyelinating neuropathy is difficult, because electrophysiological findings suggestive of demyelination are frequently observed even in patients with neurolymphomatosis. Here, we report a patient with de novo CD5‐positive diffuse large B‐cell lymphoma (DLBCL) who presented with Guillain–Barré syndrome (GBS)‐like neuropathy. Demyelination due to paraneoplastic neuropathy was clinically suspected. However, autopsy demonstrated that the cause of the neuropathy was neurolymphomatosis. Clinical courses of neurolymphomatosis vary and neurolymphomatosis cases presenting with GBS‐like neuropathy are reported. In addition, DLBCL is the most frequent histological type of malignant lymphoma that develops neurolymphomatosis. Furthermore, "CD5‐positive" DLBCL may tend to develop neurolymphomatosis. If a patient with "CD5‐positive" DLBCL develops peripheral neuropathy, neurolymphomatosis should be considered and imaging studies performed and, if possible, nerve tissue biopsy, regardless of clinical symptoms of the neuropathy. To our knowledge, this is the first report of a patient with de novo CD5‐positive DLBCL with neurolymphomatosis who presented with GBS‐like neuropathy.